RapidMic: Rapid Computation of the Maximal Information Coefficient. (January 2014) - Tang, Dongming; Wang, Mingwen; Zheng, Weifan; Wang, Hongjun
To discover relationships and associations rapidly in large-scale datasets, we propose a cross-platform tool for the rapid computation of the maximal information coefficient based on parallel computing methods. Through parallel processing, the provided tool can effectively analyze large-scale biological datasets with a markedly reduced computing time. The experimental results show that the proposed tool is notably fast, and is able to perform an all-pairs analysis of a large biological dataset using a normal computer. The source code and guidelines can be downloaded fromhttps://github.com/HelloWorldCN/RapidMic .